1999
DOI: 10.1016/s0008-6363(99)00054-1
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular systolic function and ventricular interaction during acute embolisation of the left anterior descending coronary artery in sheep

Abstract: LAD embolisation not only results in a significantly diminished LV systolic function but also causes RV systolic function to decline significantly. Regional dysfunction by necessity entails global dysfunction as well. Analysis of ventricular geometry reveals that both the septum and the RV free wall increase their length, which plays an important role in the pathophysiology of diminished RV systolic function concomitant with reduced LV function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The role of the right ventricle has largely been ignored in MI studies; however, recent studies have revealed that diminished right ventricular function has been observed as a consequence of the ischemic LV. 39 As a result, we believe that the stress incurred in the ␣-E-cat cKO right ventricle by the MI was sufficient to cause free wall rupture. Because similar infarct sizes were observed in ␣-E-cat cKO and WT mice, this further reinforced that the molecular disruptions within the adherens junction complex are key factors regulating the structural susceptibility of the ventricle.…”
Section: Discussionmentioning
confidence: 95%
“…The role of the right ventricle has largely been ignored in MI studies; however, recent studies have revealed that diminished right ventricular function has been observed as a consequence of the ischemic LV. 39 As a result, we believe that the stress incurred in the ␣-E-cat cKO right ventricle by the MI was sufficient to cause free wall rupture. Because similar infarct sizes were observed in ␣-E-cat cKO and WT mice, this further reinforced that the molecular disruptions within the adherens junction complex are key factors regulating the structural susceptibility of the ventricle.…”
Section: Discussionmentioning
confidence: 95%
“…LV PV loops shifted to the right, in agreement with experiments. 17 Because outflow of the RV was larger than that of the LV (LV outflow was reduced), pulmonic pressures and volumes were increasing, and thus preload of the LA and LV increased. This in turn increased LV end-diastolic pressures and volumes (which results in the right-shift of the loops).…”
Section: Physiological Resultsmentioning
confidence: 99%
“…This phenomenon has also been shown experimentally. 17 Owing to reduced LV outflow, systemic volumes were decreasing. But because RV outflow was also reduced, flow into the RA was still larger than outflow of the RA, increasing RA volume.…”
Section: Physiological Resultsmentioning
confidence: 99%
“…Recently, MRI-derived LV pressure-volume loops were proposed as an alternative to conductance catheter techniques by Pattynama et al 20 and then applied by Jerzewski et al 24,25 to the RV. A similar MRI approach was used in the present study.…”
Section: Technical Aspects Of This Studymentioning
confidence: 99%
“…26 Unfortunately, this method would be limited to patients without intracardiac shunts. In the studies by Pattynama et al 20 and Jerzewski et al, 24,25 pressure-volume loops were derived with multislice cine MRI during 2 different steady-state conditions of preload. Changes in preload were achieved by infusion of nitroprusside or by volume loading.…”
Section: Technical Aspects Of This Studymentioning
confidence: 99%